Multiple GPCR Functional Assays Based on Resonance Energy Transfer Sensors - Zhou, Yiwei; Meng, Jiyong; Xu, Chanjuan; Liu, Jianfeng (Frontiers in Cell and Developmental Biology, 2021)
G protein-coupled receptors (GPCRs) are the largest membrane proteins. They are important drug targets, participating in various physiological and pathological activities. While accumulating structural evidence has revealed that GPCR conformational changes occur during activation, as well as receptor activation dynamics in GPCR complexes, novel GPCR functional assays and sensors have been developed over the past two decades. This review summarizes the GPCR functional assays that recognize differential structural rearrangements, including conformational changes in GPCR/G protein and GPCR/β-arrestin complex, intra-GPCR monomers, and inter-GPCR dimers. The combinations of bioluminescence resonance energy transfer (BRET) and fluorescence resonance energy transfer (FRET) technologies have been optimized using various labeling strategies, increasing the sensitivity and compatibility of GPCR sensors from heterogeneous systems to endogenous levels. These advances have shed light on new mechanisms for GPCRs not identified by classical functional assays and have led to significant breakthroughs in both the study of the GPCR activation process and high-throughput drug screening toolboxes.